Hubungan Pengetahuan Ibu Balita Usia 7-36 Bulan Tentang Asi Eksklusif Dengan Kegagalan Ibu Dalam Memberikan Asi Eksklusif - Muniati murniati; Yuliana Puspita Dewi (Akbid Harapan Mulya Ponorogo, 2018)
Knowledge of Exclusive Breast Milk affects the mother's mindset in giving Exclusive Breastmilk to her baby. According to data from posyandu of Jalen Village, Balong District, Ponorogo District, 2016 until October for Exclusive Breastfeeding achievement of 8% from target 60%. Based on preliminary study results from 10 respondents found 3 mothers understand about Exclusive breastfeeding and exclusive breastfeeding because breast milk is very beneficial for the baby, while 7 mothers do not understand about exclusive breastfeeding and not give exclusive breastfeeding for various reasons. To know the relationship of knowledge of mother toddlers aged 7-36 months about Exclusive breastfeeding with mother failure in giving exclusive breastfeeding. The type of this research is analytic with cross sectional approach by using acidental sampling technique. Population in this research is all mother of children aged 7-36 months in Posyandu Jalen Village a number of 40 respondents with the number of samples 31 respondents in January 2017. Independent variables are maternal knowledge and dependent variable is a failure Mother of toddlers. His instruments used questionnaires and interviews. Data analysis using chi square significant is determined with value ˂0,05. From the results of the study, less knowledge about Exclusive Breast Milk most of the 16 respondents (51.6%) had and to provide Exclusive Breast Milk most of the respondents (67.7%) failed. there is correlation of knowledge of mother of toddler age 7-36 month tengtang exclusive breastfeeding with mother failure in giving exclusive breast feeding ρ = 0,024 with significance level ρ˂0,05 ho is rejected which means and level of relationship of moderate Ie 0.441 (0.400-0.599).Judging from the results of the above research is expected to have good knowledge of mothers, that is made the counseling-extension and seek information from various sources so that the mother's failure to provide an exclusive ation to her baby to be low.